ETIKA PENDIDIKAN SEKS BAGI ANAK MENURUT ABDULLAH NASHIH ‘ULWAN - Nunung Nurjanah; Tanto Aljauharie Tantowie (Tarbiyat al-Aulad: Jurnal Pendidikan Islam Anak Usia Dini, 2019)
This literature research aims to find out Abdullah Nashih ‘Ulwan's views on sex education for children. The results showed that: First, educational ethics are all actions that are in accordance with ethics in the world of education, so as to form qualified and moral human beings. Educational ethics that must be taught to children in general, namely the ethics of children to parents, the personal ethics of a student, the ethics of children to teachers, and the ethics of children when learning. Second, the ethics of sex education that is appropriate for children according to Abdullah Nashih 'Ulwan, namely: 1) Teach ethics asking permission to enter (into the room of parents and others) within 3 times, namely: a) before the dawn prayer, because that time is the time when the husband and wife are still in bed, b) noon, because usually at that time is the time the husband / wife strips off their marriage with their partner, and c) after the evening prayer, because that time is the time to sleep and rest. 2) Ethics see as: ethics sees mahram, ethics sees fiancee, ethics sees wife, ethics sees women who are not mahram, ethics of men sees men, ethics of women sees women, ethics of non-Muslim women sees Muslim women, ethics of seeing children teenagers who are handsome, women's ethics see men who are not mahram, ethics see the genitals of small children, forced situations that are allowed to see, see with the aim to treat, and see with the aim of giving decisions and testimonies in court. 3) Keep the child away from anything that leads to sex; and 4) Teach the child the syar'i laws relating to adolescence and adulthood